Resumption of Economic Growth or ‘Tail wind’? A Comparison between Brazil’s Post-neoliberalism and Mexico’s Neoliberalism (2003 - 2015) - Zunino Ruso, Antonino Pablo (2022)
This article synthesizes part of the results of research on the political and economic dynamics from Brazil and Mexico between 2003 and 2015, comparing progressive governments in the first case and neoliberal governments in the second. This article seeks to determine to what extent their different growth rates were either due to a favorable external context (marked by the rise of commodities exported by the region) or the result of discrepancies in the policies applied. The economic regulation implemented in each case is characterized, and the impact of the variation of their terms of trade on their economic performance is considered. Conclusions indicate that there were significant differences in the policies of each government; however, their differences in terms of economic growth have external origins.